The Implementation of English School Examination of Speaking and Writing Skills in The Upper Secondary Level of Education in Bandung, West Java - Andang Saehu; Utami Widiawati; Johannes A. Prayogo; Effendi Kadarisman (Universitas Negeri Malang, 2016)
Abstract: This study aims at investigating the ways the English teachers develop the test prompts of and the ways they administer the English US of speaking and writing skills. This study uses the principles of quantitative and qualitative research designs. Utilizing these principles, this present study involved 73 SMAs (30% of 243 SMAs) which were selected using a stratified random sampling technique, they were 41 SMAs from Bandung municipality and 32 SMAs from Bandung regency. Data were collected using questionnaire, interview guide, and document. The findings showed that all researched schools in Bandung, implemented the English US of speaking and writing skills. The administrative aspects, were successfully administered. However, the technical aspects, were not administered appropriately. It is due to the fact that the majority of English teachers did not involve any experts and students for the validation and the try-out of the test prompt. Key Words: English School Examination, test prompt, scoring rubric, score interpretation Abstrak: Penelitian ini bertujuan untuk menliti guru Bahasa Inggris dalam mengembangkan soal ujian dan cara guru Bahasa Inggris dalam menjalankan Bahasa Inggris US dalam kemampuan berbicara dan menulis. Penelitian ini menggunakan desain kuantitative dan kualitative. Penelitian ini melibatkan 73 SMA (30% dari total 243 SMA) yang dipilih menggunakan teknik stratified random sampling dan terpilih 41 SMA dari Kota Bandung dan 32 SMA dari Kabupaten Bandung. Data dalam penelitian ini dikumpulkan menggunakan kuisioner, interview, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa seluruh sekolah di Bandung menggunakan Bahasa Inggris US dalam kemampuan berbicara dan menulis. Aspek administrasi dijalankan secara sukses. Namun, untuk aspek teknis masih belum dijalankan dengan baik. Hal ini dikarenakan guru Bahasa Inggris tidak melibatkan ahli dan siswa untuk validasi soal try-out. Kata kunci: ujian sekolah Bahasa Inggris, soal ujian, rubrik penilaian, interpretasi penilaian